Death rattle: reassuring harbinger of imminent death or a perfect example of inadequacies in evidence-based practice. Issue 4 (December 2019) - Watts, Tessa; Willis, Derek; Noble, Simon; Johnston, Bridget
Abstract : Purpose of review: Death is the inevitable consequence of life. Although clinicians are unlikely to accurately pinpoint when death is likely to occur in the people they care for, the death in a person with a diagnosis of malignant and nonmalignant tends to involve a period of predictable progressive clinical and functional deterioration. During this time, it is common for death rattle to occur. Due to its presentation, death rattle can cause stress and distress to caregivers. This often prompts clinicians to consider medical interventions that are not only ineffective in treating the problem but may also do harm. Recent findings: There is a dearth of research related to the management of death rattle. Summary: The article discusses the existing evidence in the management of death rattle, considerations for clinicians in the absence of reliable evidence and suggests areas for future research.